Analisis Kelayakan Usaha Warung Mie Ayam Asymie Wonopringgo - Mursalina, Rizqi; Abadi, Muhammad Taufik (CV. Kalimasada Group, 2023)
The food stall business is a business that has quite large and promising opportunities. Food stalls can also be used as a place for buyers to relax, gather and so on which makes buyers have a reason to come to the food stall. That is why many people open food stalls, especially chicken noodle stalls. The purpose of this study is to find out and analyze the business feasibility of the asymie chicken noodle shop. This research use desciptive qualitative approach. The data obtained is in the form of primarydata, namely interviews and secondary data, namely observation. The research was conducted at Asymie Wonopringgo Chicken Noodle Warung. The results of the study show that when viewed from the market and marketing aspects according to the feasibility study, the asymie chicken noodle shop is very good. This can be seen from the good service, the many facilitiesand the characteristics of the product with full chicken meat topping provided by the Asymie chicken noodle shop. In addition, the price offered is also affordable for consumers of all ages according to the market segment and the promotion is carried out very well, namely through WhatsApp Story